Analysis And Manufacturing Composite For Brake Shoes Of Motorcycle Using Wood Powder, Coconut Shell Charcoal, And Copper Powder With Phenolic Matrix - Insan., Asep Sholeh Fakhrul (2012)
Brakes are very important part of the vehicle in supporting aspects of driving safety, brakes should be able to stop the vehicle as quickly as possible, and provide comfort. The objectives of this research was to investigate the influence of the use of wood powder, coconut shell charcoal, and copper powder with phenolic matrix as a material brake Shoes, brake Shoes wear and tear as well as investigating the amount of power needed by the motor when the rotating disc and investigate the resulting hardness. Research carried out by preparing all the materials and mix with 3 different variations discussed the specified composition. Later in the press with a load 3 tons for 30 minutes and heated with a temperature 1200C for 30 minutes. After the specimens were finished later in the test friction force with a weight 15 kg for 30 minutes and measured motor power, brake temperature, disc rotation, and braking time also Brinell hardness test with force 15.625 kg. Brinell hardness test result generated that violence resulting from brake Shoes Variation 1 has a value of 14.47 BHN and brake Shoes Variation 2 has a value of 14.3 BHN greater than brake Shoes Indopart has a value of 13.7 BHN, while for Variation 3 has a value of 12.6 BHN is smaller than Indopart.